Proteksi Kebocoran Gas LPG Rumah Tangga Berbasis Mikrokontroler (Komputika : Jurnal Sistem Komputer, 2022)
ABSTRACT – The use of gas fuels such as LPG is commonly used for household needs. This type of LPG is flammable, so it is necessary to be careful in its installation and use. Along with the development of technology and to minimize the occurrence of LPG leaks, a tool that is able to protect gas leaks is needed as a fire trigger that works automatically. The protection device is built using an Arduino-based microcontroller, the main sensor is MQ2. The way it works the MQ2 sensor will detect LPG if there is a leak, then the sensor sends a signal to the microcontroller, and the microcontroller will give instructions to the relay, where the relay acts as an automatic switch to activate the solenoid valve sensor so that it closes the LPG flow, thus the LPG flow stops to protect the occurrence fire, besides that a buzzer sounds as a notification of an LPG leak. From the results of this study, MQ2 detects LPG with levels of 0 ppm to 1280 ppm and LPG is still supplied, when LPG levels are detected between 5240 ppm to 26464 ppm, LPG supply stops because the solenoid valve blocks the LPG flow